ANALYSIS OF THE EFFECT OF USING VIRTUAL TRY-ON BASED ON ARTIFICIAL INTELLIGENCE AND AUGMENTED REALITY ON FACIAL BEAUTY PRODUCTS ON PURCHASE INTENTION WITH ELECTRONIC WORD OF MOUTH AS A MEDIATION VARIABLE (CONSUMER PERSPECTIVE OF E-COMMERCE IN INDONESIA) - Fenanda, Zakiah Intan; Triwijayanti, Anna; Wahyono, Seno Aji (Lembaga Penelitian dan Pengabdian Masyarakat, Institut Teknologi Nasional (ITN) Malang, 2024)
This research aims to determine the effect of Virtual Try On on consumer Purchase Intention mediated by eWOM. The method used in this research is quantitative explanatory research. The population in this research is Indonesian e-commerce consumers who use the virtual try-on feature for facial beauty products, an unknown number of which are unknown. The sample in this study was obtained from the Hair formula in the amount of 10 x the number of questionnaire items, namely 240 people. Data collection used a questionnaire survey with the pick-up survey method. Data analysis uses the SEM PLS (Partial Least Square) analysis technique. The research results show that the Virtual Try On variable has a significant positive effect on eWOM, eWOM has a significant positive effect on Purchase intention, Virtual Try On has a significant positive effect on purchase intention directly and is also mediated by eWOM and the effect is complementary (partial mediation).